Nurses´competences in preventive cardiology - Chloubová, Iva; Tóthová, Valérie (Magyar Egészségügyi Szakdolgozói Kamara, 2019)
The goal of the article consists in presenting the results of the analysis of the available sources focused on nurse education and the resulting competences in the field of cardiology, as well as in describing the system of health-educational activities of nurses in preventive cardiology in selected EU countries.
Keywords: nurse; competence; preventive cardiology; cardiovascular diseases